2016
DOI: 10.12968/jowc.2016.25.7.393
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma, bilayered acellular matrix grafting and negative pressure wound therapy in diabetic foot infection

Abstract: The authors have received no financial support for the material presented in this study outside of the scope of standard patient care reimbursement. This work was supported by the National Natural Science Foundation of China (NO. 81500596) awarded to Dr Wuquan Deng.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…87 In another study, PRP gel was found to be superior to antiseptic ointment dressing. 88 Similar positive effects on accelerating the healing of infected wounds has also been demonstrated in clinical trials, 89,90 even showing efficacy in patients with severe arterial disease. 91…”
Section: Treatment For Chronic Ulcersmentioning
confidence: 62%
“…87 In another study, PRP gel was found to be superior to antiseptic ointment dressing. 88 Similar positive effects on accelerating the healing of infected wounds has also been demonstrated in clinical trials, 89,90 even showing efficacy in patients with severe arterial disease. 91…”
Section: Treatment For Chronic Ulcersmentioning
confidence: 62%
“…Combined with the application of NPWT, bilayered acellular matrix grafting, and split-thickness skin grafting, APG shows obvious effectiveness in foot necrotizing fasciitis and gaseous gangrene. 10 NPWT could facilitate wound healing by promoting tissue perfusion and providing a moist local environment for wound coverage. 31,32 Additionally, wound healing is not the ultimate goal of DFU management.…”
Section: Discussionmentioning
confidence: 99%
“…The exposed bone had been successfully closed although there was no significant reduction in the size of ulceration ( Figure 1C). After full evaluation and informed consent was obtained, autologous platelet-rich gel (APG) was prepared as described in our previous study 10 (Figure 2A) and the gel was administered to the surface of the wound ( Figure 2B). After 10 days, granulation tissues gradually grew in the ulcer cavity.…”
Section: Case Reportmentioning
confidence: 99%
“…The causes of chronic skin wounds include a complex combination of local and systemic factors, such as circulatory dysfunction, infection, wound duration, malnutrition, endocrine‐metabolic disturbances, aging, and immunodeficiency . Although multidisciplinary treatments are necessary for chronic wounds and various methods of treatment have been employed for years, some cases remain refractory to existing treatments, and the wound healing processes do not progress for unclear reasons …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although multidisciplinary treatments are necessary for chronic wounds and various methods of treatment have been employed for years, some cases remain refractory to existing treatments, and the wound healing processes do not progress for unclear reasons. [5][6][7][8][9] Hochu-ekki-to (HET; Bu-Zhong-Yi-Qi-Tang in Chinese) is a traditional Japanese herbal medicine that originated in China and is commonly used to treat severe weakness, loss of appetite, and indigestion in elderly patients and to prevent opportunistic infections in infection-prone patients. [10][11][12][13][14] Basic research has reported improvement of leukopenia, IgE antibody production and inhibitory action, antiviral action via activation of natural killer T cells, and protective action against bacterial infection with the use of HET.…”
Section: Introductionmentioning
confidence: 99%